P2P overlay support for ubiquitous Web 2.0 - Anwitaman Datta (2010)
The original objective of the project was to explore the fundamental and conceptual challenges, as well as carry out implementation in realizing a peer-topeer overlay based application layer internet, which will facilitate Web 2.0 applications and services in a network and device independent manner. The work carried out within the context of the SuG itself comprised on mainly exploring conceptual problems – particularly algorithms for overlay design – for efficient content discovery and dissemination in peer-to-peer settings.